Konsep Keselamatan Dalam Al-Qur'an - Salamah Eka Susanti (Institut Ilmu Keislaman Zainul Hasan Genggong, 2018)
The doctrine of salvation is an important concept that is common to every religion. Therefore, each religion claims to be the savior (Salvator) for each of its followers. In Protestant Christianity for example, there is a doctrine known as